Recent advances of the thermodynamic behavior of Tin species in aqueous solution - Yang, Dongrong; Wu, Zhilian; Ren, Kun; Dong, Peng; Zhang, Da; Yang, Bin; Liang, Feng (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
Thermodynamic behavior has been extensively used to evaluate the stability of materials and predict the direction of the chemical reaction at different pH values, temperatures, potentials, and ion concentrations. Although researching efforts on Tin species in an aqueous solution system (Tin/H2O of acid, alkali, and salt have been reported, scattered data leads to the inefficiency of a thermodynamic method in the practical application. This article provides a brief review about the potential-pH diagram for Tin/H2O system, which reflects the thermodynamic behavior of Tin species in an aqueous solution and extracts thermodynamic data for Tin species for its practical application. Firstly, the relationship of the thermodynamic behavior, potential-pH diagram, and equilibrium relations of Tin species for Tin/H2O system was overviewed. Additionally, the potential-pH diagram of Tin/H2O system at different temperatures (298 K, 373 K, and 550 K) and dissolved Tin activities (1, 10−1, 10−3, and 10−6) and the potential-pH diagram of the Tin species in a chloridion aqueous solution system (Tin/H2O-Cl) was summarized. Finally, the application prospect of the potential-pH diagram for Tin/H2O system is prospected in the intelligent simulation of Tin metallurgy and the practical application of Tin materials.